Analisis faktor-faktor yang mempengaruhi pemanfaatan Lembaga Amil Zakat Al-Ihsan Jawa Tengah Cabang Utama Solo 2009 - AJI, Agung Siswanto Bayu ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The law number 38, 1999 on Management of Zakat gives an opportunity to people to get involved in managing zakat (charity) through the formation of Lembaga Amil Zakat (LAZ). LAZ Al-Ihsan Central Java, Solo branch (LAZiS), it is one LAZ that is formed based on the law mentioned above. As a non profit institution, the existence of LAZiS is determined by the donation given by the community. The reason of muzakkis (zakat givers) use LAZiS to deliver their donation or charit y because they believe that LAZiS manages the collected fund and distribute them correctly. The trust is a valuable asset for LAZiS. Without any trust from the community, especially the donators, the existence of LAZiS will be threatened. The aim of this study is to analyze the correlation between physical, service, communication variables and the trust variable. The number of respondents is 50 persons that use the service of LAZiS and their professions are government officials and the employees of BUMN. The result of the data analysis shows that the correlation strength of the three variables and the trust variable that have been studied, it indicates that the physical variable has a weak level of relationship with the trust variable; while the service and co mmunication variables have a medium level of relationship with the trust variable. Meanwhile, based on the data analysis on categorical regression obtains result that simultaneously, a 53.7 percent variation of trust variable can be explained by the physical, service and communication variables.